Patents in the Food Sector A Retrospective with Special Emphasis on the TRIPs Agreement - Willnegger, Eva (Munich Intellectual Property Law Center - MIPLC, 2008)
Interestingly enough, food, being central to every human being, has been excluded from pat-entability in many patent laws. The Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPs) now forces all Members of the World Trade Organization to abolish the exemption. For this reason, this study looks at the Patent Acts of Germany, Brazil, China, and India in a comparative law approach with respect to the exemption to patentability of food-related inventions and the effects of its abolition. Secondly, it describes the food sector of today and particularly its technological developments. Finally, the intellectual property situation of the food sector is analyzed.